A Risk Model Composed of Complete Blood Count, BRAF V600E and MAP2K1 Predicts Inferior Prognosis of Langerhans Cell Histiocytosis in Children - Wang, Leyuan; Yuan, Lin; Du, Xizi; Zhou, Kai; Yang, Yu; Qin, Qingwu; Yang, Liangchun; Xiang, Yang; Qu, Xiangping; Liu, Huijun; Qin, Xiaoqun; Liu, Chi (Frontiers in Oncology, 2022)
Background In children, Langerhans cell histiocytosis (LCH), which is the most prevalent histiocytic disorder, exhibits a wide variety of manifestations and outcomes. There is no standard prognosis evaluation system for LCH. We investigated the combined predictive significance of complete blood counts (CBCs), BRAF V600E and MAP2K1 in childhood LCH. Methods A cohort of 71 childhood LCH patients was retrospectively studied. The prognosis predictive significance of platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), systemic inflammation response index (SIRI), systemic immune inflammation index (SII), BRAF V600E, and MAP2K1 were analyzed. Results Histiocyte Society (HS) classification of LCH patients was correlated with NLR, SIRI, and progression free survival (PFS), bone involvement was correlated with SIRI, liver involvement was correlated with NLR, SII, SIRI, and PFS, spleen involvement was correlated with SIRI, lung involvement was correlated with NLR and PFS, CNS involvement was correlated with PFS, while BRAF V600E was correlated with PLR, NLR, SIRI, SII, PFS, and OS (p <0.05). MAP2K1 was correlated with NLR, SIRI, PFS, and OS (p <0.05). Elevated NLR, PLR SIRI, and SII predicted inferior PFS and OS (p <0.05). PLR, NLE, SIRI, SII, BRAF V600E, and MAP2K1 were used to establish a risk model for stratifying the LCH patients into 3 different risk groups. Respective median PFS for low-, mediate-, and high-risk groups were not reached, 26, and 14 months (p <0.001), and all median OS were not reached (p <0.001). Conclusion The risk model combined with CBCs, BRAF V600E, and MAP2K1 might be a promising prognostic system for LCH in children.